2021
DOI: 10.22550/rep79-1-2021-09
|View full text |Cite
|
Sign up to set email alerts
|

El cultivo inteligente de las emociones morales en la adolescencia

Abstract: This article examines the relationship between emotional intelligence, emotional competence, and emotional education, with special reference to moral emotions applied to secondary education. Emotional education is a continuous and permanent educational process that occurs throughout life with the objective of developing emotional competences. Emotional intelligence in education is the foundation of these competences. There is currently abundant evidence for the benefits for students of emotional education. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
127

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(148 citation statements)
references
References 2 publications
0
21
0
127
Order By: Relevance
“…In these situations, teams score more points in the first possession and, conversely, concede more points in the subsequent three possessions. Anger is an emotion that provides energy and, depending on the cause, can generate anxiety and frustration [ 36 , 37 ], which can have a negative effect on the concentration and confidence of athletes—particularly in the face of external causes [ 38 ], such as a refereeing decision. Zur, Cooke, Woodman, Neil, and Udewitz [ 39 ], in their study of elite fencing athletes, found very similar results; initially, anger improved the reaction time of athletes, but subsequently reduced their performance.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, teams score more points in the first possession and, conversely, concede more points in the subsequent three possessions. Anger is an emotion that provides energy and, depending on the cause, can generate anxiety and frustration [ 36 , 37 ], which can have a negative effect on the concentration and confidence of athletes—particularly in the face of external causes [ 38 ], such as a refereeing decision. Zur, Cooke, Woodman, Neil, and Udewitz [ 39 ], in their study of elite fencing athletes, found very similar results; initially, anger improved the reaction time of athletes, but subsequently reduced their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Negative emotions are more intense and longer-lasting than positive emotions [20]. The literature shows that negative events and interactions have a disproportionately greater effect on variables such as satisfaction with life, mood, health, and stress than positive events and interactions [19,21,22].…”
Section: The Predictive Power Of Acceptance and Rejection Experiences...mentioning
confidence: 99%
“…The scientific bibliography has highlighted how the domain of emotional competences impacts cognition, memory, attention, decision making, behaviors, moral evaluations, health, etc. [1,[33][34][35][36]. For all these reasons, emotional competences are understood as basic competencies for life and their development extends throughout the entire life cycle, being considered essential during the first stages of life.…”
Section: Emotional Competencies Evaluation Modelsmentioning
confidence: 99%